PHOSPHOR IMAGING AS A TOOL FOR IN SITU MAPPING OF PPM LEVELS OF URANIUM AND THORIUM IN ROCKS AND MINERALS - Cole J.M.; Nienstedt J.; Spataro G.; Rasbury E.T.; Celestian A.J.; Hanson G.N.; Lanzirotti A.; Nilsson M. (My University, 2002)
Phosphor imaging is a type of digital autoradiography that has been widely used in biochemistry to examine radioactively tagged proteins. We used phosphor imaging to map in situ U and Th in polished slabs of geological materials including carbonates, phosphates, and silicate-rich rocks. We examined samples containing between 2 and >500 ppm U and ∼700 ppm Th to evaluate the applicability of the technique to geological samples. Resolution of 1 mm or better was obtained even for low concentration (∼10 ppm) samples. These analyses are routine and only require a light box, phosphor screen, and access to a phosphor imager. The technique is nondestructive, relatively inexpensive, and requires very little processing time. We used this technique to identify U- and Th-enriched carbonates and phosphates, and to find “hot spots” of U- and Th-rich minerals in a granodiorite. These high-resolution maps of U and Th allow us to effectively sample for geochronology and identify potentially interesting samples for synchrotron X-radiation studies. The maps produced by phosphor imaging also have great potential for investigating the details of adsorption of radionuclides to rocks and minerals in contaminated areas.